Identification of AhFatB genes through genome-wide analysis and knockout of AhFatB reduces the content of saturated fatty acids in peanut (Arichis hypogaea L.). (June 2022) - Tang, Yanyan; Huang, Jianbin; Ji, Hongchang; Pan, Leilei; Hu, Changli; Qiu, Xiaochen; Zhu, Hong; Sui, Jiongming; Wang, Jingshan; Qiao, Lixian
Abstract: Peanut ( Arachis hypogaea L.) is an allotetraploid oilseed crop worldwide due to its abundant high-quality oil production. Peanut oil stability and quality are determined by the relative proportions of saturated fatty acids (SFAs) and unsaturated fatty acids (UFAs). The principle approach to minimize the content of SFAs in peanut is to reduce the content of palmitic acid, which is linked to cardiovascular disease. Acyl-acyl carrier protein thioesterases (FATs) determine the types and levels of fatty acids that are exported them from the plastids. Two different classes of FAT have been classified into two families in plants, FatA and FatB . Among them, AhFatB has become the primary objective to genetically reduce the content of palmitic acid in peanut. Here, we identified 18 AhFatB genes in A. hypogaea genome and grouped into four major subfamilies through gene structures and phylogenetic relationships. Expression profiling of AhFatB genes was assessed using the publicly available RNA-seq data and qRT-PCR in 22 tissues. Using the CRISPR/Cas9 system, we designed two sgRNAs to edit the homologs AhFatB genes Arahy.4E7QKU and Arahy.L4EP3N, and identified different types of mutations. Additionally, we discovered mutations at Arahy.4E7QKU exhibited low palmitic acid and high oleic acid phenotypes. The obtained peanut mutants with altered SFAs content have great potential for improving peanut oil quality for human health. Highlights: A total of 18 AhFatB members were characterized in Arachis hypogaea L. Mutations of AhFatB showed low palmitic and high oleic acid using CRISPR/Cas9 system. AhFatB determined the oil profile and improved oil quality in peanut.